PREVENTION OF LOSS OF CEMENT ACTIVITY DURING TRANSPORTATION AND STORAGE - Safarova Ruxshona Ulug‘bek qizi; Bekov Ulug’bek Safarovich (Web of Journals Publishing, 2024)
In this article discusses, the addition of 0.2% naphthalene soap or 0.1% oleic acid as a hydrophobizing agent to maintain the properties of cement during transportation and storage, and the production of commercially produced hydrophobized cements is studied.